The association between tea consumption and blood pressure in the adult population in Southwest China - Ying Zhao; Chengmeng Tang; Wenge Tang; Xuehui Zhang; Xiaoman Jiang; Zhuoma Duoji; Yixi Kangzhu; Xing Zhao; Xiaohe Xu; Feng Hong; Qiaolan Liu (BMC, 2023)
Abstract Objectives Prior research on the effect of tea consumption on blood pressure (BP) generated inconsistent findings. The objective of this study was to explore the effects of different types of tea consumption on BP. Methods We included 76,673 participants aged 30-79 from the baseline data of the China Multi-Ethnic Cohort (CMEC) study. Binary logistic regression was used to analyze the influences of different types of tea consumption on the risk of hypertensive BP. Moreover, multiple linear regression was used to examine the association between tea drinking and BP. Results Tea consumption was associated with a reduced risk of hypertensive BP by 10% (AOR: 0.90, 95%CI: 0.86-0.94). While dark tea was related to a 1.79-5.31 mmHg reduction in systolic blood pressure (SBP) and a 0.47-1.02 mmHg reduction in diastolic blood pressure (DBP), sweet tea, regardless of the duration, frequency, or amount of consumption, significantly was associated with a reduced SBP by 3.19-7.18 mmHg. Green tea also was associated with a reduced SBP by 1.21-2.98 mmHg. Although scented tea was related to reduced SBP by 1.26-2.48 mmHg, the greatest effect came from the long duration (> 40 years:β=-2.17 mmHg, 95%CI=-3.47 mmHg --0.87 mmHg), low frequency (1-2 d/w: β = -2.48 mmHg, 95%CI=-3.76 mmHg--1.20 mmHg), and low amount (≤ 2 g/d: β=-2.21 mmHg, 95%CI=-3.01 mmHg--1.40 mmHg). Additionally, scented tea was correlated to a decrease in DBP at the frequency of 1-2 d/w (β=-0.84 mmHg, 95%CI=-1.65 mmHg--0.02 mmHg). Drinking black tea only was associated with lowered SBP. The protective effect of black tea on SBP was characterized by the long-duration (> 15 years, -2.63--5.76 mmHg), high frequency (6-7 d/w, -2.43 mmHg), and medium amount (2.1-4.0 g/d, -3.06 mmHg). Conclusion Tea consumption was associated with lower SBP and a reduced risk of hypertensive BP. The antihypertensive effect varies across types of tea consumed.